Correlation of depression and anxiety with smartphone addiction among medical clerkship - I Gde Yudhi Kurniawan; Luh Nyoman Alit Aryani; I Made Rustika; Lely Setiawati (Journal of Clinical and Cultural Psychiatry, 2021)
Background: Smartphone is a mobile phone with operating system and internet access that has many functions and can be helpful for medical clerkship students to finish their assignments and as well as an entertainment media. Excessive and uncontrolled use of smartphone may lead to smartphone addiction. Depression and anxiety might correlate with smartphone addiction. The goal of this study was to determine the correlation of depression and anxiety with smartphone addiction among medical clerkship students in Bali province. Materials and Methods: The research was an observational non-experimental study with cross sectional design, and descriptive analytic analysis. Samples were obtained by systematic sampling. Instruments used were the Modified Smartphone Addiction Scale Indonesian version and Depression Anxiety Stress Scale 42 (DASS 42). Data were analyzed by Spearman’s test then simple regression analysis for anxiety and smartphone addiction because depression did not fulfill assumption test. Results: A number of 100 samples were analyzed. Depression was positively correlated to smartphone addiction (r=0.542, p <0.001). Anxiety was positively correlated to smartphone addiction (r=0.598, p <0.001). Simple regression analysis showed a value of R=0.591 (p <0.001) and as such anxiety played role on smartphone addiction. A determination coefficient of 0.349 showed the effective role of anxiety on smartphone addiction was 34.9% whereas the remaining 75.1% was determined by another variable that were not investigated on this study. Conclusion: There was a significant positive relationship with the strength of a moderate relationship between depression and anxiety with smartphone addiction.